2023
DOI: 10.21203/rs.3.rs-2503035/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

TNFα induces matrix metalloproteinase-9 expression in monocytic cells through ACSL1/JNK/NF- kB signaling pathways

Abstract: Background Studies have established the association between increased plasma levels of matrix metalloproteinase (MMP)-9 and adipose tissue inflammation. Tumor necrosis factor α (TNFα) was elevated in obesity and is involved in the induction of MMP-9 in monocytic cells. However, the underlying molecular mechanism was incompletely understood. As per our recent report, TNFα mediates inflammatory responses through long-chain acyl-CoA synthetase 1 (ACSL1). Therefore, we further investigated the role of ACSL1 in TN… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Previous research has demonstrated that broin affects both NF-kB driven in ammation and wound healing [5,6,22]; therefore, the propensity for SDP to activate the canonical NF-kB signaling pathway was investigated as a baseline for bioactivity. The nuclear transcription factor p65 is part of the NF-kB complex, which translocates into the cell nucleus upon activation to facilitate pro-in ammatory gene expression, including TNF-α and MMP-9 [34]. The NF-kB pathway was stimulated within HCLE cultures using TNF-α, and then treated with increasing doses of SDP.…”
Section: Sdp Inhibits Activation Of the Nf-kb In Ammatory Pathwaymentioning
confidence: 99%
“…Previous research has demonstrated that broin affects both NF-kB driven in ammation and wound healing [5,6,22]; therefore, the propensity for SDP to activate the canonical NF-kB signaling pathway was investigated as a baseline for bioactivity. The nuclear transcription factor p65 is part of the NF-kB complex, which translocates into the cell nucleus upon activation to facilitate pro-in ammatory gene expression, including TNF-α and MMP-9 [34]. The NF-kB pathway was stimulated within HCLE cultures using TNF-α, and then treated with increasing doses of SDP.…”
Section: Sdp Inhibits Activation Of the Nf-kb In Ammatory Pathwaymentioning
confidence: 99%
“…Such proin ammatory factors collectively degrade the ocular surface through disruption of the mucin protein coating, which provides the foundation for a stable and hydrating protective tear lm (5,6). In ammatory mediators regulated by NF-κB, such as matrix metalloprotease (MMP)-9, tumor necrosis factor alpha (TNF-α), and interleukin (IL)-8, have been found at high concentrations in the tear uid in patients exhibiting severe DED (7)(8)(9). Topical administration of MMP-9 to DED-MMP-9-knockout mice subjected to dry eye via cholinergic blockade signi cantly increases corneal epithelial permeability, implicating MMP-9 in increased corneal epithelial disruption and damage (10).…”
Section: Introductionmentioning
confidence: 99%